ОЛИЙ ЎҚУВ ЮРТЛАРИ ИЛМИЙ ВА ИННОВАЦИОН ФАОЛИЯТИНИ ТИЖОРАТЛАШТИРИШНИ ТАКОМИЛЛАШТИРИШ - Ҳакимов, Н.Ҳ.; Бекбаев, Г.А. (SCIENCE and SOCIETY, 2022)
The article analyzes the role of the reform of the higher education system of the Republic of Uzbekistan at a new stage of development of society. The authors tried to reveal the purpose, content and essence of the structural reforms carried out in the university system at the present stage. The article is based on the international experience of training a new corps of qualified personnel, the importance of the regulatory framework regulating the scientific and innovative activities of the teaching staff in the reform of higher education. The article examines the content of the commercialization of the results of scientific works, which was considered as factors of improving the quality indicators of the process of accelerating the educational, scientific activity of the teaching staff.